Sistem Informasi Penjualan Kapal pada Kabupaten Tanah Laut Berbasis Web Mobile - Ayu Faradillah; Yunita Prastyaningsih (mijournal.org, 2025)
Tanah Laut District is an area that has the potential of the sea that is promising for regional income. In coastal areas, many people have ships. The process of economic turnover for ship buying and selling is also profitable. The plot, if the ship owner wants to create a new type of ship, want to stop at sea or change domicile the owner can do the sale of the vessel. The sales process of the current vessel is done by giving information orally to fellow ship owners to be notified to the public if there are those who are looking for a ship to buy. The solution to this problem is to create a ship sales information system in the land-based Mobile Web. This information system is designed with Unified Modeling Language (UML), built with the PHP programming language Database, MySQL and using the Waterfall method. Vessel sales Information System in Tanah Laut District can facilitate the ship sellers in marketing the ship and facilitate the buyer to find the vessel to be bought. Data collected in the form of 3 types of vessels and 10 data vessels.